The Estimation of Sediment Dynamics in Mae Chaem River Basin Using SWAT Model - Triritthiwittaya, Prangtip; Ekkawatpanit, Chaiwat; Kositgittiwong, Duangrudee; Kompor, Wongnarin (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 27, 2022)
Natural erosion and deposition of sediment along the Mae Chaem River bank area caused by the fluctuated stream flowing through channel segments. The effect of rainfall on soil particles, particularly during the rainy season, causes the soil surface to be washed and moved down the river. Furthermore, sediment transport can destabilize river banks and have an impact on ecosystems, people’ livelihoods, and land use management along riversides. As a result, the objective of this study is to assess the daily flow and sediment transport of the Mae Chaem Basin from 2004 to 2013 using the Soil Water Assessment Tool (SWAT) model. Furthermore, utilizing the Sequential Uncertainty Fitting 2 (SUFI-2) technique, the SWAT-CUP program was used to emphasize the sensitivity of parameters in a hydrological model. The discharge of model results was calibrated using station 061302 as the inlet and stations P.14 and P.14A as the outlets, with stations 061302 and P.14 also serving as sediment measuring stations. The statistical values of the Coefficient of determination (R2) and the Nash–Sutcliffe model efficiency coefficient (NSE) were in range of 0.82 to 0.46 for calibration and validation periods of sediment evaluation. Furthermore, sediment load simulation revealed that the majority of sediment deposition occurred in the middle of Mae Chaem District, whereas bank erosion was intensely formed downstream, covering the area of Kong Khaek Sub-district, Mae Chaem District, and Bo Luang Sub-district, Hot District, Chiang Mai province.